Top management's green transformational leadership and competitive advantage: the mediating role of green organizational learning capability - Ozgul, Burcu; Zehir, Cemal (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose - This study aims to develop an original green organizational learning capability (GOLC) framework to examine the effects of green transformational leadership (GTL) on competitive advantage (CA) through GOLC by making use of the natural resource-based view (NRBV). Design/methodology/approach - The current research proposes GOLC as a novel construct that simultaneously integrates green absorptive capability (GAC) and green transformative capability (GTC). Furthermore, this study presents a theoretical model that investigates GOLC as an intermediate mechanism in the relationship between GTL and CA based on the NRBV. The partial least squares method is used to test the data collected from 265 firms included in the list of Turkeys Top 500 Industrial Enterprises in 2019 and having ISO 14001 certificate. Findings - Top management's GTL positively affects the firm's GOLC. Moreover, GOLC positively affects the firm's CA. This study further shows that GIL has a significant indirect effect on CA through GOLC. Practical implications - This study demonstrates how firm managers can be persuasive in adopting GOLC with a critical role in developing and promoting green products and services to improve the firm's environmental sustainability and CA by exhibiting GTL. Originality/value - This research applies the NRBV theory to propose a novel concept, GOLC and develops an integral conceptual model to discover its managerial impacts, antecedent and consequence. No prior literature has examined the impact of top management's GTL on GOLC and CA.
Keywords: Green transformational leadership; Green absorptive capability; Green transformative capability; Competitive advantage; ABSORPTIVE-CAPACITY; INNOVATION PERFORMANCE; PRODUCT INNOVATION; AFFECT MARKET; CREATIVITY; ORIENTATION; KNOWLEDGE; PERSPECTIVE; UNCERTAINTY; STRATEGY; Business & Economics